De la violence à l’école à l’école de la violence. Essai d’analyse de la pratique pédagogique comme forme de violence - Joseph Avodo (Sociétés et Jeunesses en Difficulté)
Study of violence proposed in this paper is based on the assumption of the existence of potential violence in the teacher discourse. Through the practice, teacher runs some forms of violence called here educational or rationalized violence. Educational violence can be defined as verbal aggression and psychological control on the learner. It can affect the motivation of learner and his relationship with his teacher. Educational violence is a hidden form of violence. The problem which this type of violence is the link between interactional models exposed to school and youth training.